Regional Development and Interregional Migration Decisions in Jakarta - . Hamzah Nurdin; . Sukanto; . Yunisvita (Модернизация, инновация, развитие, 2022)
Purpose: this study aims to examine the community's decision to migrate between regions in the Jabodetabek area using the KRL Commuterline public transportation and analyse regional criteria based on regional development based on Oriented Development Transit, where these criteria become integration with community movements in migrating to an area.Methods: secondary data is used to fnd the number of people in migrating obtained from pt. Kai Indonesia. While to complete and explain each variable to be studied using primary data with several questions through a questionnaire submitted to 398 people who migrate between regions using logistic regression analysis techniques in their measurements. While to analyze the criteria for regional development in each region using an assessment approach from the Institute for Transportation and Development Policy. With qualitative analysis techniques and to assist in this research, a spatial approach is used which is used to display a picture of the distribution of migration.Results: (1) Regional development in each part of the Jabodetabek area is in the silver standard category which indicates that the regional development project has almost met the performance targets that have been conceptualized by the Institute for Transportation and Development Policy. (2) People in making decisions to migrate between regions will be aﬀected by the variables of distance, travel costs, gender, travel time, migration destination and regional development, while age and transit distance cannot provide a large enough inﬂuence on people's movements in migrating.Conclusions and Relevance: the results of the study prove that regional development in the Jabodetabek area tends to be a non-metropolitan area where people who move prefer areas that are integrated with public facilities that lead to the destination rather than towards the metropolitan area, this is evidenced by the standard silver criteria obtained in the area in Jabodetabek.